Temperature, health and wellbeing in Australia - Hailemariam, Abebe; Churchill, Sefa Awaworyi; Appau, Samuelson (My University, 2023)
We examine the effects of temperature on general health and subjective wellbeing. We combine daily temperature data with 19 waves of panel data from the Household, Income and Labour Dynamics in Australia Survey. We find evidence of an inverted U-shaped relationship between temperature and general health. However, the effect of temperature on subjective wellbeing is less robust. We examine whether the adoption of air conditioning technology moderates the observed relationship between temperature and health. Our results show that there is no robust evidence for the role of air conditioning in moderating the relationship between temperature and health/wellbeing. Further, we conducted a mediation analysis to examine whether sleep quality serves as a channel through which the effect of temperature transmits to health. We find little evidence in support of sleep quality as a mechanism.
Journal of Behavioural Economics
Keywords: Health and wellbeing; Housing, communities and neighbourhoods